1979
DOI: 10.1007/bf00233651
|View full text |Cite
|
Sign up to set email alerts
|

Development of the structural components of the brush border in absorptive cells of the chick intestine

Abstract: The spatial and temporal relationships between cytoplasmic filaments and the morphogenesis of the intestinal brush border were examined by transmission electron microscopy of normally developing tissue and of tissue exposed to a variety of experimental conditions in organ culture. Distinct stages in the development of the brush border were identified: (1) Irregular projections of the apical plasma membrane that contain a network of microfilaments are converted to uniform projections filled with a core bundle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 42 publications
4
49
1
Order By: Relevance
“…The authors suggested that the amount of digestible isoleucine in diets became insufficient when viscera meal in the diet was over 5%. El-Sheikh et al (1996) indicated that the supplementation of methionine and lysine to broiler diets containing viscera meal increased nitrogen use and performance. Alleman et al (2000) offered a plausible explanation for the reduced performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that the amount of digestible isoleucine in diets became insufficient when viscera meal in the diet was over 5%. El-Sheikh et al (1996) indicated that the supplementation of methionine and lysine to broiler diets containing viscera meal increased nitrogen use and performance. Alleman et al (2000) offered a plausible explanation for the reduced performance.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the inclusion of animal byproducts reduced digestion and absorption of fats, which can be justified by the lower inclusion of soybean oil in diets. Besides, on the first posthatch days, chicks are not completely mature to digest and absorb nutrients, especially fat (Chambers & Gray, 1979;Moran Jr., 1994;Krogdahl & Sell, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Early research on BB cytoskeleton formation focused on embryonic chickens, mice and rats (Chambers and Grey, 1979;Ezzell et al, 1989;Maunoury et al, 1988;Rochette and Haffen, 1987;Shibayama et al, 1987;Stidwill and Burgess, 1986;Takemura et al, 1988), with subsequent work utilizing cell lines (Dudouet et al, 1987;Peterson et al, 1992). Recently, attention has turned to understanding the development of the BB in adult tissues.…”
Section: Brush B O R D Er a S S E M B L Y In In Te S Tin A L C R Yptsmentioning
confidence: 99%
“…Microvilli, similarly to pollen tubes or fungal hyphae, look like regular cylinders with a dome-shaped apex (see electron micrographs: Mooseker and Tilney, 1975;Chambers and Grey, 1979;Hirokawa et al, 1982). Filopodia may also look like this (see Bridgman and Dailey, 1989, Fig.…”
Section: Cellsmentioning
confidence: 99%
“…There are numerous indications that the arrangement of actin filaments is not strict in cell outgrowths. For instance, while the central filaments in mature microvilli are arranged in longitudinal bundles, at the early stage of the outgrowths' development they usually form an unstructured network (Chambers and Grey, 1979;Tilney and Jaffe, 1981). Bundles of filaments were absent both in thin processes (Savion and Selinger, 1978) and in lamellar evaginations (Andrews, 1976).…”
Section: Cellsmentioning
confidence: 99%